2020
DOI: 10.3390/nano10030488
|View full text |Cite
|
Sign up to set email alerts
|

A Perfect Absorber Based on Similar Fabry-Perot Four-Band in the Visible Range

Abstract: A simple metamaterial absorber is proposed to achieve near-perfect absorption in visible and near-infrared wavelengths. The absorber is composed of metal-dielectric-metal (MIM) three-layer structure. The materials of these three-layer structures are Au, SiO 2 , and Au. The top metal structure of the absorber is composed of hollow three-dimensional metal rings regularly arranged periodically. The results show that the high absorption efficiency at a specific wavelength is mainly due to the resonance of the Fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…The diffraction peaks of ZnO correspond to (100), (002), (101), (102), (110), (103) and (004) crystal orientation, respectively [55][56][57]. Among them, the diffraction peaks of WO 3 correspond to the crystal orientations of (100), (110), (102) and (120) at 18.88°, 24.47°, 30.48° and 38.37°, respectively [58,59]. By comparison, it was found that the value of the (100) crystal orientation peak was the highest, meaning that the growth of WO 3 along the (100) crystal plane was dominant.…”
Section: Xrdmentioning
confidence: 99%
“…The diffraction peaks of ZnO correspond to (100), (002), (101), (102), (110), (103) and (004) crystal orientation, respectively [55][56][57]. Among them, the diffraction peaks of WO 3 correspond to the crystal orientations of (100), (110), (102) and (120) at 18.88°, 24.47°, 30.48° and 38.37°, respectively [58,59]. By comparison, it was found that the value of the (100) crystal orientation peak was the highest, meaning that the growth of WO 3 along the (100) crystal plane was dominant.…”
Section: Xrdmentioning
confidence: 99%
“…Thereby, the photoexcited e − could be migrated to Ag quickly, and the photoinduced h + still situated on Ag 3 PO 4 nanoparticle and ZnO nanorods, which promoted the separation of photoexcited e − -h + effectively. As illustrated in Figure 6b, the enriched e − on Ag nanocrystals could promote the multiple-e − reduction reaction effectively, the corresponding reaction formula is as follows [62][63][64], O 2 + 4H + + 4e − → 2H 2 O.…”
Section: #mentioning
confidence: 99%
“…MMAs also can be found in IR [65], lower MIR [66], UV [67], THz [68], [69], GHz [70], MHz [71], KHz [72], Hz [73] with visible/optical region as discussed above with applications like STPV [74], [75], light trapper [76], cryptography [77], thermal detector [78], sound absorption [79], underwater sound absorption [80], detectors [81], military radar devices [81], detection of explosives [82], photonic circuit [83], filter [84], refractive index sensor [85], reflector [86], thermal imaging [87], antenna [88], light detection [89], [90], energy harvesting [91], [92], imaging [93], [94], sensors [95]- [98].…”
Section: Introductionmentioning
confidence: 99%